Fullerene and apoptosis - M. A. Orlova; T. P. Trofimova; A. P. Orlov; O. A. Shatalov; Yu. K. Napolov; A. A. Svistunov; V. P. Chekhonin (Онкогематология)
Fullerene derivatives superfamily attracts a serious attention as antiviral and anticancer agents and drug delivery carriers as well. A large number of such fullerene С60 derivatives obtained to date. However, there is an obvious deficit of information about causes and mechanisms of immediately and long-term consequences of their effects in vivo which is a true obstacle on the way leading to practical medical use of them. First, this concerns their impact on the proliferation, apoptosis and necrosis regulation. Fullerene nanoparticle functionalization type, their sizes and surface nanopathology are of great importance to further promoting of either cytoprotective or cytotoxic effects. This lecture provides modern concept analysis regarding fullerenes effects on apoptosis pathway in normal and tumor cells.